2015
DOI: 10.5001/omj.2015.34
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Questionnaire Measuring Quality of Life in Menopausal Women: A Systematic Review

Abstract: Menopause is a natural part of the aging process in women and is defined as occurring 12 months after the last menstrual period marking the end of menstrual cycles. Menopause has a negative impact on the quality of life (QoL). Various generic and specific questionnaires have been used for assessing different dimensions of QoL in menopausal women. The purpose of this systematic review was to identify those general and specific instruments, and to determine the factors that affect QoL in menopausal women. We ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 58 publications
3
47
0
7
Order By: Relevance
“…The other commonly used scales include 36-item short-form (SF-36), World Health Organization Quality of Life (WHOQOL-BREF), Utain Quality of Life Scale (UQOL), Woman's Health Questionnaire (WHQ) and Greene Climacteric Scale. However in a systematic review by Jenabi et al, MenQol was found to be most validated and most commonly used scale in literature and this is the same scale we have used in our study [10].…”
Section: Number Of Patients Percentagementioning
confidence: 99%
See 1 more Smart Citation
“…The other commonly used scales include 36-item short-form (SF-36), World Health Organization Quality of Life (WHOQOL-BREF), Utain Quality of Life Scale (UQOL), Woman's Health Questionnaire (WHQ) and Greene Climacteric Scale. However in a systematic review by Jenabi et al, MenQol was found to be most validated and most commonly used scale in literature and this is the same scale we have used in our study [10].…”
Section: Number Of Patients Percentagementioning
confidence: 99%
“…menopausal symptoms, as experienced over the last month: vasomotor (items 1-3), psychosocial (items 4-10), physical (items 11-26), and sexual (items 27-29). Items pertaining to a specific symptom are rated as present or not present, and if present, how bothersome on a zero (not bothersome) to six (extremely bothersome) scale [10]. All the data were noted on the proforma.…”
Section: Methodsmentioning
confidence: 99%
“…Calidad de vida (CV) es un concepto multidimensional y multifactorial cuyo rol como indicador ha emergido con importancia en el área de la salud (1,2) . Durante el climaterio, algunas mujeres experimentan un conjunto de síntomas relacionados con la menopausia que afectan negativamente la CV: oleadas de calor, sudores nocturnos, alteraciones del sueño, cansancio, sequedad vaginal y depresión, entre otros (2) .…”
Section: Introductionunclassified
“…Durante el climaterio, algunas mujeres experimentan un conjunto de síntomas relacionados con la menopausia que afectan negativamente la CV: oleadas de calor, sudores nocturnos, alteraciones del sueño, cansancio, sequedad vaginal y depresión, entre otros (2) .…”
Section: Introductionunclassified
See 1 more Smart Citation